Morfologia do coração de girinos de rãs-touro Lithobates catesbeianus (SHAW, 1802), expostas ao piretro, encapsulado ou não em nanopartículas - Magalhâes, Rielly de Cássia (Universidade Federal de São Carlos, 2021)
The increase in agricultural and industry activities, as well as in the emission of urban effluents with no treatment have been an issue of particular concern regarding the health of freshwater bodies and their organisms due to the increase of xenobiotics in the aquatic environments. Currently, technological advances have allowed action to be taken to mitigate the impacts of these substances on non-target organisms. Among them, it is worthy to mention the nanocareer-systems (as the solid lipid nanoparticles – SLN), which encapsulate active components, such as pesticides, liberating them in a modified and more controlled manner. However, additional studies are still needed to evaluate the potential risk, mechanism of action and toxicity of nanopesticides on non-target organisms, considering that these pollutants can lead to a reduction of the adaptive value of organisms, among other negative impacts to their survival. The aim of this work was to evaluate the cardiac morphophysiology (myofibrils’ diameter) in response to the exposure (48 h) to SLN and to the biocide pyrethrum, isolated and associated. The results demonstrated that the diameter of cardiac myofibrils increased (P < 0.05) in response to the exposure to all xenobiotics in relation to the control, indicating a cardiac hypertrophy. Indeed, the hypertrophy was more accentuated (P < 0,05) in the cardiac myocytes of the individual exposed to the pyrethrum associated to the SLN than was these compounds were tested isolated. This alteration may result in an increase in the cardiac output by increases in the systolic volume, representing a strategy to raise the blood flux to organs, maximizing the xenobiotics detoxification process. Therefore, we demonstrated that pyrethrum and solid lipidic nanoparticles, isolated and associated, result in adaptive responses in the species even at sublethal concentrations and under acute exposure. It can be strongly suggested that these substances should be controlled to minimize the decline in amphibians’ populations.
Cardiac morphology of Lithobates catesbeianus bullfrogs (SHAW, 1802) exposed to pyrethrum free and encapsulated in nanoparticles
Keywords: Miócitos; Biocidas; Nanocarreadores; Anfíbios anuros; myofibrils; biocides; nanocareers; anuran amphibians; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA COMPARADA